Analisa Dana Transfer Pusat dan Probabilitas Terjadinya Korupsi di Tingkat Pemerintah Daerah - Aan Dwi Nurcahyo; Benedictus Raksaka Mahi (Komisi Pemberantasan Korupsi, 2022)
The majority of corruption in the regions in Indonesia is carried out on Regional Budget funds, which the main source of Regional Budget revenue comes from Central Government transfers. Based on the characteristics of their use, transfer funds can be classified into General Purpose Transfers (DTU) and Specific Purpose Transfers (DTK). This study was conducted to see the influence of DTU and DTK on the probability of corruption in the regions. The method used is Zero-Inflated Poisson (ZIP) regression because there is an overdispersion problem and excess zero in the dependent variable. With a sample of 519 Regency and City Governments in Indonesia in the 2010-2019 period, DTU was found to have a positive relationship to the level of corruption. The flexibility in managing the DTU budget is the cause that triggers an increase in corruption in the regions. Meanwhile, DTK shows a negative relationship with the level of corruption. The local government does not have the flexibility to use the DTK budget for other programs, and the supervision in the realization of the DTK program is also tighter.